2011
DOI: 10.2174/156800911793743583
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Vaccination with a Therapeutic EGF-Based Cancer Vaccine: A Review of Patients Receiving Long Lasting Treatment

Abstract: Therapeutic vaccines continue to be one of the most active fields in cancer research. However, despite clear evidence of antitumor effect in laboratory animals, and despite the ability of current vaccine candidates to elicit tumor specific antibodies and T-cells in humans, objective responses in the clinical trials are rare. The role of therapeutic vaccines in advanced cancer patients, if any, would be to decrease the rate of disease progression and to increase survival and quality of life. Due to the redundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…Vaccines, known as therapeutic cancer vaccines, are being developed to treat patients with existing cancer and are one of the most active fields in cancer research [110]. Treatment with cancer vaccines, an active immunotherapy for cancer, is a desired method for cancer patients, especially patients with cervical cancer as cervical cancer is caused by viruses, for example, human papillomavirus (HPV).…”
Section: Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccines, known as therapeutic cancer vaccines, are being developed to treat patients with existing cancer and are one of the most active fields in cancer research [110]. Treatment with cancer vaccines, an active immunotherapy for cancer, is a desired method for cancer patients, especially patients with cervical cancer as cervical cancer is caused by viruses, for example, human papillomavirus (HPV).…”
Section: Vaccinationmentioning
confidence: 99%
“…Clinical trials showed that the therapeutic telomerase-(TERT-) specific vaccine Vx-001 could induce TERT-reactive T cells and have a significant overall survival benefit in patients with chemoresistant advanced solid tumors [114]. A therapeutic vaccine, composed of epidermal growth factor (EGF) chemically conjugated to a carrier protein from Neisseria meningitides, induced anti-EGF antibody titters, decreased EGF concentration in plasma, and had survival advantages in vaccinated patients with advanced lung cancer [110]. However, there are currently no therapeutic vaccines available to treat cancers effectively.…”
Section: Vaccinationmentioning
confidence: 99%
“…The metanalysis of 58 patients who were vaccinated monthly for more than one or two years evidenced that long term vaccination was feasible and safe, without evidences of cumulative toxicity or immune response exhaustion [65]. The results of the planned interim analysis with the first 226 patients recruited in the ongoing randomized phase III trial, vaccinating the patients who respond to first line chemotherapy with at least stable disease, in the modality of switch maintenance, beyond progression disease and until change their performance status as per physician criteria, confirm previous results in benefit the patient’s overall survival by intent to treat analysis (manuscript in preparation).…”
Section: Cancer Vaccines Medical Positioning In the Current Nsclc CLImentioning
confidence: 99%
“…The concern is justified by the growth stimulating property of these active principles. Practically, antigrowth factor therapy is approved or extensively experimented for several neoplasia (Gonzalez et al, 2011;Caraglia et al, 2006;Geva et al, 2010). Additionally an increase in any-site cancer incidence was observed in DFU patients treated with platelet-derivedgrowth factor (PDGF; becaplermin), which generated a warning from regulatory agencies (FDA-USA, 2008).…”
Section: Overview Of Safetymentioning
confidence: 99%